Determination of the Active Power Filter Type Based on the Component to be Compensated - Selin OZCIRA (Gazi Üniversitesi Fen Bilimleri Dergisi, 2018)
Power converters affected by nonlinear loads cause the current from the grid. Because of this harmonic distortion current and voltage wave forms of grid becomes sum of the fundamental component and other sinusoidal components having different frequency and amplitude. Design of active power filters with the recent advances in microcontroller technologies has gained momentum in order to use the electrical energy in a more efficient way by removing the harmonic effects on the grid caused by nonlinear electrical loads or by compensating the distortive effects of the grid in order to prevent the load to be affected. In this study, available active power filter topologies in literature have been classified and three different types of filters have been simulated by using p-q instantaneous power theory to create a comparison table in which the selection criteria of active power filters based on the component to be compensated have been stated.